Personal messages to Professor B.J. van der Walt - Letšosa, R. (Koers, 2010)
Professor B.J. van der Walt: a very complex and dynamic configuration of a variety of functions centrally religiously directed in all his actions Voor Bennie en Hannetjie van der Walt: herinneringen aan meer dan 40 jaren vriendschap B.J. van der Walt: consummate educator